Nature and scope of change within post-socialist Polish enterprises - Stępień, Beata; Robinson, Izabela (Economics and Business Review, 2002)
This paper examines the process of strategic management within post-socialist Polish enterprises within last five years (1995-2000). There can be no doubt as to the dramatically altered environment within which post-socialist Polish enterprises are required to compete. By the same token, the strategic orientation of post-socialist enterprises has had to change. What is less clear, however, is the nature, scope and direction of change at enterprise level and the specific drivers of strategic change. What explanations can be found for the fact that enterprises within the same industry, subject to similar environmental pressures, have chosen significantly different paths to adjustment with entirely diverse results? How exactly can we differentiate the strategies adopted by transforming enterprises both immediately after the dismantling of the socialist system and more recently? The aim of our research was to provide answers to these questions. We begin by evaluating evidence of enterprise restructuring during the initial period of transformation and move on to present empirical evidence as to the strategic direction of a sample of post-socialist Polish firms during the last five years of transformation. We see this as a significant period in the transformation process as enterprises move away from a 'wait and see' cautious approach to the one which demonstrates a greater awareness of the need for a proactive strategy in adjustment to the free market conditions. Our paper presents a critical appraisal of enterprise adjustment and focuses on the nature and scope of change within post-socialist Polish enterprises within the following areas: • changes in ownership and their impact on the enterprise, • changes in market orientation and segmentation, • developments in strategy formulation, • changes in work processes and the management of people. (original abstract)